Slurry for positive electrode of lithium iron phosphate battery, electrode of lithium iron phosphate battery, lithium iron phosphate battery and manufacturing method of lithium iron phosphate battery
By doping ternary materials and rare earth oxides in the lithium iron phosphate positive electrode slurry and using specific organic additives, the problems of low slurry active content and poor stability in the prior art are solved, and the battery electricity is significantly improved Chemical properties and cycle life.
Patent Information
- Application Number
- CN202411281986.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
AI Technical Summary
The existing lithium iron phosphate positive electrode slurry has low active content, poor electrochemical performance, poor stability, limited cycle life, complex pulping process and low efficiency.
Lithium iron phosphate material doped with ternary materials is used to combine with rare earth oxides, and organic mixed solutions of isopropanolamine, glycol and polyethylene glycol are used as the positive electrode organic additives, and through specific stirring and coating processes, Improves the solid content and viscosity of the slurry, and enhances compatibility and bonding between materials.
It significantly improves the active content and electrochemical performance of the positive electrode slurry, extends the cycle life of the battery, improves the stability and charge and discharge performance of the slurry. The battery's service life reaches more than 8,000 times, and the discharge specific capacity is 0.5C and Significantly improved at 1C ratio.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a slurry for a lithium iron phosphate battery positive electrode, a lithium iron phosphate battery electrode, a lithium iron phosphate battery and a manufacturing method thereof. Background Art
[0002] Lithium iron phosphate batteries have the advantages of high operating voltage, high energy density, long cycle life, good safety performance, low self-discharge rate, and no memory effect. The materials used to make lithium iron phosphate batteries have the characteristics of good safety performance, excellent cycle performance, environmental friendliness, and a wide range of raw material sources. Among them, lithium, iron, and phosphorus are all elements with abundant reserves on the earth. In particular, iron-based materials have a wide source of raw materials and are low in price. They are recognized as the preferred positive electrode material for the new generation of lithium-ion batteries and have become the focus of research and development in major developed countries in the world today. Moreover, because it is stable at high temperatures and the electrolyte used is stable, and has good high-temperature cycle performance, it is particularly suitable for power batteries. Lithium iron phosphate lithium-ion batteries have been widely developed and applied in power tools, energy storage, and electric vehicles in recent years.
[0003] At present, most of the preparation of lithium iron phosphate positive electrode slurry adopts wet pulping process. This process requires large equipment investment, complex pulping process, long pulping time, incomplete mixing and low efficiency. In order to shorten the pulping time and improve production efficiency, people have begun to explore and study dry mixing pulping process. For example, Chinese patent CN103700861B discloses a lithium-ion battery positive electrode slurry slurrying process. In this process, lithium iron phosphate and conductive agent are stirred evenly under dry mixing conditions, and then a binder, distilled water and a polymerizing agent are added for mixing and stirring. However, the content of positive electrode active material obtained by the above pulping process needs to be improved. Although the energy density and internal resistance of the battery have been improved, the overall electrochemical performance is not ideal, and the slurry stability needs to be improved, and the homogenization effect is not ideal; the cycle life is limited to 1500 times and begins to decay.
[0004] Therefore, there is an urgent need for a lithium iron phosphate battery positive electrode slurry and a production process thereof that can effectively increase the active matter content of the current lithium iron phosphate positive electrode slurry, improve the electrochemical performance, and improve the slurry stability. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a slurry for lithium iron phosphate battery positive electrode, a lithium iron phosphate battery electrode, a lithium iron phosphate battery and a method for manufacturing the same, which can significantly increase the active material content, improve the electrochemical performance and slurry stability.
[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides a slurry for positive electrode of lithium iron phosphate battery, characterized in that it comprises the following components in parts by weight:
[0007]
[0008]
[0009] The active lithium iron phosphate material is a lithium iron phosphate material doped with a ternary material, the particle size range of the lithium iron phosphate material is 2 to 6 μm, and the mass ratio of the lithium iron phosphate material to the ternary material is 5 to 8:2 to 5; the ternary material is a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.815 Co 0.15 Al 0.035 O2、LiNi 0.88 Co 0.09 Al 0.03 One of lithium nickel cobalt aluminum oxides having a molar ratio of O2 and Ni of more than 0.9, wherein the general chemical formula of the lithium nickel cobalt aluminum oxide is LiNi x Co y Al 1-x-y O2, 0.7<x<1,0<y<0.3;
[0010] The positive electrode organic auxiliary agent is an organic mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 5-7:2-3:1-2; the molecular weight of the polyethylene glycol is 200-600.
[0011] As a preferred embodiment of the present invention, the lithium iron phosphate battery positive electrode slurry comprises the following components in parts by weight:
[0012]
[0013] The active lithium iron phosphate material is a lithium iron phosphate material doped with a ternary material, the particle size range of the lithium iron phosphate material is 2 to 6 μm, and the mass ratio of the lithium iron phosphate material to the ternary material is 5 to 8:2 to 5; the ternary material is a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.815 Co 0.15 Al 0.035 O2、LiNi 0.88 Co 0.09 Al 0.03 One of lithium nickel cobalt aluminum oxides having a molar ratio of O2 and Ni of more than 0.9, wherein the general chemical formula of the lithium nickel cobalt aluminum oxide is LiNi x Co y Al 1-x-y O2, 0.7<x<1,0<y<0.3;
[0014] The positive electrode organic auxiliary agent is a mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 7:2:1; the molecular weight of the polyethylene glycol is 200-600.
[0015] As a preferred embodiment of the present invention, rare earth element oxides refer to oxides of 15 lanthanide elements with atomic numbers of 57 to 71 in the periodic table, and oxides of 17 elements including scandium (Sc) and yttrium (Y) with similar chemical properties to lanthanide elements. The molecular formula of lanthanum oxide is La O3, and the molecular weight is 325.84. Specifically, the rare earth oxide is at least one of the oxides of lanthanum, cerium, yttrium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and scandium.
[0016] As a preferred embodiment of the present invention, the rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide, and the mass ratio of lanthanum oxide, cerium oxide and neodymium oxide is 8:1:1; the particle size range of the rare earth oxide is 2-4 μm or 4-8 μm. Preferably, it is 2-4 μm. Since rare earth elements can improve battery activity by providing charge and participating in reaction, the compatibility between positive electrode materials and negative electrode materials can be enhanced, thereby improving battery performance. In addition, rare earth elements can also be used in these batteries to enhance the bonding force between materials and increase the capacity of the battery, and to improve the cycle performance and capacity retention rate of the battery.
[0017] As a preferred embodiment of the present invention, the ternary material is a high nickel ternary material LiNi 0.88 Co 0.09 Al 0.03 O2.
[0018] As a preferred embodiment of the present invention, the weight ratio of lithium iron phosphate to the ternary material is 8:2.
[0019] As a preferred embodiment of the present invention, the binder is polyvinylidene fluoride with a molecular weight of 1 million to 1.2 million.
[0020] As a preferred embodiment of the present invention, the cathode solvent is a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 1-2:8-9, and the molecular weight of the polyvinyl pyrrolidone is 10000-25000.
[0021] As a preferred embodiment of the present invention, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 1.5:8.5, and the molecular weight of the polyvinyl pyrrolidone is 10,000-25,000.
[0022] As a preferred embodiment of the present invention, the conductive agent is a mixture of one or more of carbon nanotubes, graphene, SP, and KS-6, and the particle size of the conductive agent is in the range of 2 to 4 μm.
[0023] A second object of the present invention is to provide a positive electrode for a lithium iron phosphate battery, characterized in that it is made of the above-mentioned slurry for the positive electrode of a lithium iron phosphate battery.
[0024] The third object of the present invention is to provide a lithium iron phosphate battery, characterized in that it includes the lithium iron phosphate battery positive electrode.
[0025] As a preferred embodiment of the present invention, the method for preparing the lithium iron phosphate battery is characterized by being carried out according to the following steps:
[0026] Weigh 95-97 parts of active lithium iron phosphate material, 0.1-1 parts of rare earth oxide, 1-2 parts of acetylene black, 0.5-2 parts of conductive agent, 1-5 parts of binder, 2-3 parts of positive electrode organic additive and 30-40 parts of positive electrode solvent by weight;
[0027] The binder is prepared into a glue solution using a cathode solvent;
[0028] After the weighed rare earth oxide, acetylene black and conductive agent are dry-mixed evenly, a portion of the glue solution is slowly added, and the mixture is stirred at a speed of 15 to 30 RPM for 15 to 30 minutes to obtain a mixture A;
[0029] Adding active lithium iron phosphate material and positive electrode organic additive to mixed material A in multiple times to obtain mixed material B; controlling the stirring speed to 15-80RPM in a gradient manner, and the stirring time is 1-2h;
[0030] Slowly add the remaining glue to the mixture B, with a stirring speed of 15 to 80 RPM, and stir in a gradient manner for 1 to 2 hours to obtain a slurry for a positive electrode of a lithium iron phosphate battery, wherein the solid content of the slurry for a positive electrode of a lithium iron phosphate battery is 60 to 70%, the slurry viscosity is 6000 to 12000 mPa·s, and the slurry fineness is ≤20 μm;
[0031] The prepared slurry was coated on a clean and dry aluminum foil using an extrusion coater at room temperature;
[0032] The coated electrode sheet is placed in a vacuum oven, baked at 80-120°C for 12-16 hours, and rolled and die-cut to obtain a positive electrode sheet;
[0033] The prepared electrode pieces were cut into square electrode pieces, and graphite was used as the negative electrode to prepare a full battery in a glove box filled with nitrogen.
[0034] As a preferred embodiment of the present invention, the amount of the binder is 0.5-2% of the total weight of the lithium iron phosphate, the conductive agent and the binder.
[0035] As a preferred embodiment of the present invention, the thickness of the aluminum foil pole piece is 12 to 16 μm, the coating speed of the coating machine is 8-30 m / min, the coating baking temperature is adjustable at 80 to 135°C in the front, middle and rear sections to ensure the pole piece is dry, and the coating surface density is: 167 to 230 g / ㎡ on a single side; while coating, 2 to 12 mm (PVDF + ceramic) insulating glue is coated on the edge of the pole piece material area.
[0036] As a preferred embodiment of the present invention, the electrode drying temperature is 80-120° C., and the drying time is 12-16 hours.
[0037] As a preferred embodiment of the present invention, the pole piece rolling speed is 10 to 50 m / min.
[0038] As a preferred embodiment of the present invention, the electrode film is cut into square electrode sheets as a stirring process and slurry for the full battery.
[0039] The beneficial effects of the present invention are:
[0040] (1) The positive electrode slurry has a high content of active materials, and the positive electrode sheet prepared with the positive electrode slurry has a high compaction density. In the battery material, by adding positive electrode organic additives, the electrochemical performance, energy storage performance and charge and discharge performance of the battery are significantly improved;
[0041] (2) The mixing process of rare earth oxide doped lithium iron phosphate material slurry, coating, film making and slurry preparation method improves the slurry and coating performance of positive lithium iron phosphate, improves the battery discharge performance and cycle life. The lithium iron phosphate slurry prepared by the present invention has uniform temperature, stirring process and slurry coating, smooth surface and no particles, and significantly improves the slurry stability and surface density stability; in terms of service life, the charge and discharge cycle of the lithium iron phosphate battery is increased to more than 8,000 times;
[0042] (3) The discharge capacity of the full battery at a rate of 0.5C is greater than 166 mAh / g, and the discharge capacity at a rate of 1C is greater than 159 mAh / g, which not only improves the stability of the battery slurry, but also significantly extends the service life of the battery;
[0043] (4) The coating speed of the coating machine is 8 to 30 m / min, and the coating baking temperature in the front, middle and rear stages is adjustable between 80 and 135°C to ensure that the electrode is dry and within the range of 167 to 230 g / m2 on a single side. DETAILED DESCRIPTION
[0044] The following describes the implementation of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application.
[0045] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0046] In addition, it should be understood that one or more method steps mentioned in this application do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in this application does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these two explicitly mentioned devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of implementation of this application. Changes or adjustments in their relative relationships shall also be regarded as the scope of implementation of this application without substantial changes in the technical content.
[0047] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0048] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0049] Example 1
[0050] The present embodiment provides a slurry for positive electrode of lithium iron phosphate battery, wherein the weight ratio of each component is: 96 parts of active lithium iron phosphate material; 0.7 parts of rare earth oxide; 1.5 parts of acetylene black; 1 part of conductive agent; 2.5 parts of binder; 2 parts of positive electrode organic additive; 35 parts of positive electrode solvent; the positive electrode organic additive is a mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, and the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 7:2:1; the molecular weight of the polyethylene glycol is 200; the weight ratio of lithium iron phosphate to ternary material is 8:2; the ternary material is a high nickel ternary material LiNi 0.88 Co 0.09 Al 0.03 O2; the rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide, the mass ratio of lanthanum oxide, cerium oxide and neodymium oxide is 8:1:1; the particle size range of the rare earth oxide is 2 to 4 μm.
[0051] The method for preparing the slurry for the positive electrode of a lithium iron phosphate battery described in this embodiment comprises the following steps:
[0052] Step 1, weighing 96 parts of active lithium iron phosphate material, 0.7 parts of rare earth oxide, 1.5 parts of acetylene black, 1 part of conductive agent, 1 part of binder, 2 parts of positive electrode organic additives and 35 parts of positive electrode solvent by weight;
[0053] Step 2, using a cathode solvent to prepare a binder into a glue solution, wherein the mass percentage of the binder in the glue solution is 10%; the cathode solvent is a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 1.5:8.5, and the molecular weight of the polyvinyl pyrrolidone is 10000-25000;
[0054] Step 3, dry-mix the weighed rare earth oxide, acetylene black and conductive agent, slowly add part of the glue solution, and stir and mix at a speed of 15-30 RPM for 15-30 minutes to obtain a mixture A;
[0055] Step 4, adding active lithium iron phosphate material and positive electrode organic additive to mixture A in multiple times to obtain mixture B; controlling the stirring speed to 15-80RPM in a gradient manner, and the stirring time is 1-2h;
[0056] Step 5, slowly adding the remaining glue to the mixture B, stirring at a speed of 15 to 80 RPM, stirring in a gradient manner, to obtain a slurry for a positive electrode of a lithium iron phosphate battery, wherein the solid content of the slurry for a positive electrode of a lithium iron phosphate battery is 60 to 70%, the slurry viscosity is 6000 to 12000 mPa·s, and the slurry fineness is ≤20 μm;
[0057] Step 6: Coat the prepared slurry on a clean and dry aluminum foil at room temperature using an extrusion coater; the thickness of the aluminum foil pole piece is 12-16 μm, the coating speed of the coater is 8-30 m / min, and the coating baking temperature is adjustable at 80-135°C in the front, middle and rear stages to ensure that the pole piece is dry. The coating surface density is: 167-230 g / ㎡ on a single side; while coating, 2-12 mm (PVDF+ceramic) insulating glue is applied to the edge of the pole piece material area;
[0058] Step 7: Place the coated electrode sheet in a vacuum oven, bake at 80-120° C. for 12-16 hours, roll and die-cut to obtain a positive electrode sheet; the rolling speed of the electrode sheet is 10-50 m / min;
[0059] Step 8: Cut the prepared electrode into square electrode pieces, use graphite as the negative electrode, and prepare a full battery in a glove box filled with nitrogen.
[0060] Example 2
[0061] The slurry for positive electrode of lithium iron phosphate battery used in this embodiment has the following components in weight ratio: 95 parts of active lithium iron phosphate material; 0.1 parts of rare earth oxide; 1 part of acetylene black; 0.5 parts of conductive agent; 1 part of binder; 2 parts of positive electrode organic additive; 35 parts of positive electrode solvent; the positive electrode organic additive is a mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, and the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 7:2:1; the molecular weight of the polyethylene glycol is 600; the weight ratio of lithium iron phosphate to ternary material is 7:3; the ternary material is a high nickel ternary material LiNi 0.88 Co 0.09 Al 0.03 O2. The rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide, and the mass ratio of lanthanum oxide, cerium oxide and neodymium oxide is 8:1:1; the particle size range of the rare earth oxide is 2-4 μm. The method for preparing a lithium iron phosphate battery using the lithium iron phosphate battery positive electrode slurry of this embodiment is the same as that of embodiment 1.
[0062] Example 3
[0063] The present embodiment provides a slurry for positive electrode of lithium iron phosphate battery, wherein the weight ratio of each component is: 97 parts of active lithium iron phosphate material; 1 part of rare earth oxide; 2 parts of acetylene black; 2 parts of conductive agent; 5 parts of binder; 2 parts of positive electrode organic additive; 35 parts of positive electrode solvent; the positive electrode organic additive is a mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, and the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is: 7:1.5:1.5; the molecular weight of the polyethylene glycol is 200; the weight ratio of lithium iron phosphate to ternary material is 8:2; the ternary material is a high nickel ternary material LiNi 0.88 Co 0.09 Al 0.03The rare earth oxide is a mixture of lanthanum oxide, cerium oxide and yttrium oxide, the mass ratio of lanthanum oxide, cerium oxide and neodymium oxide is 8:1:1; the particle size range of the rare earth oxide is 2-4 μm.
[0064] The method for preparing a lithium iron phosphate battery using the lithium iron phosphate battery positive electrode slurry of this embodiment is the same as that of Example 1.
[0065] Example 4
[0066] The difference between Example 4 and Example 1 is that the ternary material is a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2, the rest of the process is exactly the same.
[0067] Example 5
[0068] The difference between Example 5 and Example 1 is that the ternary material is a high-nickel ternary material LiNi 0.95 Co 0.015 Al 0.035 O2, the rest of the process is exactly the same.
[0069] Example 6
[0070] The difference between Example 6 and Example 1 is that the positive electrode organic additive ratio is different, the positive electrode organic additive is an organic mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, and the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 6:2:2. The rest of the processes are exactly the same.
[0071] Example 7
[0072] The difference between Example 7 and Example 1 is that the molecular weight of the polyethylene glycol in the positive electrode organic additive is 300. The rest of the processes are exactly the same.
[0073] Example 8
[0074] The difference between Example 8 and Example 1 is that the proportion of the cathode solvent components is different, the cathode solvent is a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 1:9, and the molecular weight of the polyvinyl pyrrolidone is 20000. The rest of the processes are exactly the same.
[0075] Example 9
[0076] The difference between Example 9 and Example 1 is that the proportion of the cathode solvent components is different, the cathode solvent is a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 2:8, and the molecular weight of the polyvinyl pyrrolidone is 20000. The rest of the processes are exactly the same.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 1 is that lithium iron phosphate material is used to replace the active lithium iron phosphate material, and the other processes are exactly the same.
[0079] Comparative Example 2
[0080] The difference between Comparative Example 2 and Example 1 is that no rare earth oxide is added, and the other processes are exactly the same.
[0081] Comparative Example 3
[0082] The difference between Comparative Example 3 and Example 1 is that no positive electrode organic additive is added, and the other processes are exactly the same.
[0083] Comparative Example 4
[0084] The difference between Comparative Example 4 and Example 1 is that isopropanolamine is used to replace the positive electrode organic additive, and the other processes are exactly the same.
[0085] Comparative Example 5
[0086] The difference between Comparative Example 5 and Example 1 is that ethylene glycol is used to replace the positive electrode organic auxiliary agent, and the other processes are exactly the same.
[0087] Comparative Example 6
[0088] The difference between Comparative Example 6 and Example 1 is that N-methylpyrrolidone is used to replace the positive electrode solvent, and the rest of the processes are exactly the same.
[0089] Comparative Example 7
[0090] The difference between Comparative Example 7 and Example 1 is that polyvinyl pyrrolidone is used to replace the positive electrode solvent, and the other processes are exactly the same.
[0091] Full batteries were prepared using the lithium iron phosphate battery positive electrode slurry obtained in Examples 1 to 9 and Comparative Examples 1 to 7; the results are shown in Tables 1 and 2 below.
[0092] The present invention indicates the dispersion and consistency of the slurry by the fluctuation range of the viscosity and fineness of the slurry. The smaller the fluctuation range, the better the dispersion and consistency of the slurry. The viscosity and fineness of each sample are measured 20 times with a time interval of 2 minutes to see the fluctuation range of 20 times. The viscosity is measured by a viscometer and the fineness is measured by a scraper fineness meter. The test results are shown in Table 1.
[0093] Table 1 Performance test results of lithium iron phosphate battery positive electrode slurry
[0094]
[0095]
[0096] It can be seen from the above table that the viscosity fluctuation range and fineness fluctuation range of the positive electrode slurry for lithium iron phosphate batteries provided in the embodiments of the present invention are relatively small; for example, the viscosity of the positive electrode slurry in Example 1 is 9844mPa·s, and the fineness fluctuation range is 7-8μm; relative to Comparative Examples 1-7, the viscosity and fineness fluctuation range of the slurry of the present invention are small, indicating that the dispersibility and consistency of the slurry are good. It can be seen from the comparison between Example 1 and Example 4, Example 5 and Comparative Example 1 that doping ternary materials in lithium iron phosphate materials can significantly improve the viscosity and solid content of the slurry. As the nickel content in the ternary material increases, the viscosity of the positive electrode slurry increases. However, when the nickel content in the ternary material increases to more than 0.9, the viscosity increase trend of the slurry slows down, and the slurry fineness fluctuation range widens. Therefore, when the ternary material is doped with a high-nickel ternary material LiNi in the lithium iron phosphate material, the viscosity of the positive electrode slurry increases. 0.88 Co 0.09 Al 0.03 O2, the dispersibility and consistency of the slurry are the best; from Example 1, Examples 6 to 9 and Comparative Examples 3-7, it can be seen that the proportion of the positive electrode solvent component and the proportion of the positive electrode organic additive in the positive electrode slurry for lithium iron phosphate battery will affect the dispersibility of the positive electrode slurry, especially the content of N-methylpyrrolidone in the positive electrode solvent component is high, the fineness fluctuation range of the obtained slurry is large, and the stability and dispersibility are reduced. When the positive electrode organic additive is not added, the viscosity of the positive electrode slurry is 5260mPa·s, and the fineness fluctuation range is 5-11μm, while after adding the positive electrode organic additive, it is obvious The dispersibility and consistency of the positive electrode slurry are improved by at least 1.8 times, and the stability of the entire slurry is also significantly improved. However, if only isopropanolamine or ethylene glycol is added to the slurry respectively, the viscosity of the slurry also increases, but the increase is slow. Therefore, it can be seen that if the various components in the positive electrode organic additive are used alone, although the performance of the slurry is improved to a certain extent, the performance improvement is not significant enough. When the various components in the positive electrode organic additive are added together in a specific ratio, they play a role of coordination and synergy, which significantly improves the dispersibility and consistency of the positive electrode slurry.
[0097] The present invention performs performance tests on full batteries prepared with the slurry for positive electrodes of lithium iron phosphate batteries obtained in Examples 1 to 9 and Comparative Examples 1 to 7; the test results are shown in Table 2 below.
[0098] Table 2 Lithium iron phosphate battery electrical performance test results
[0099]
[0100] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 7 that the slurry prepared by this method has better uniformity, the particle size in the conductive slurry is uniform, and its dispersibility and stability are better. When the content of active material lithium iron phosphate is 95 to 97 parts, the compaction density of the positive electrode sheet, the energy density of the battery and other comprehensive performances are excellent, and the performance of the full battery prepared by using active lithium iron phosphate material is significantly improved compared with that prepared directly using lithium iron phosphate material. By doping ternary materials such as nickel cobalt aluminum oxide in the lithium iron phosphate material, the battery discharge specific capacity can be improved. It can be seen from Examples 1 to 9 that the content of active lithium iron phosphate material is increased. Although the internal resistance of the battery is increased, the compaction density of the positive electrode sheet, the battery energy density and the discharge specific capacity at 0.5C rate and 1C rate are significantly improved. The comprehensive performance of the battery made of the positive electrode slurry of the present invention is significantly improved. This is because the positive electrode organic additive can dissolve the active substances in the electrode materials such as lithium iron phosphate, making it easier to carry out electrochemical reactions and improve the performance of the battery. In addition, the positive electrode organic additive can improve the structure of the electrode material, improve the energy storage performance, charge and discharge performance and charging rate of the battery. When the amount of positive electrode organic additive added is 2 parts, the cycle life of the battery is increased by more than 30%, the charge and discharge performance is improved by 5 times, and the charging rate is also greatly improved.
[0101] From Examples 1 to 3 and Comparative Example 2, it can be seen that adding rare earth oxides to lithium iron phosphate materials is beneficial to stabilizing the crystal structure of the raw materials, improving the reversible capacity and cycle performance, and improving high and low temperature performance. Since the rare earth atom radius is large, it will increase C, which means that the interlayer spacing becomes larger, so it has a faster Li + Insertion and migration capabilities, better charge and discharge stability. It plays a role in expanding the lithium ion insertion and removal channels and stabilizing the skeleton structure. It has been verified that it has a high reversible capacity and good cycle performance. It has strong high and low temperature adaptability and can be used in an environment of -20℃--60℃.
[0102] The positive electrode solvent of the present application adopts a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, which can be used as a dispersant for the positive electrode conductive agent to effectively disperse the conductive agent to obtain a positive electrode slurry with excellent performance, and can also improve the battery's rate performance and increase the battery capacity of charge and discharge.
[0103] In summary, these factors do not work alone, but work in coordination to significantly improve the electrical performance of the battery. The discharge capacity of the full battery at a rate of 0.5C is greater than 166mAh / g, and the discharge capacity at a rate of 1C is greater than 159mAh / g, which not only improves the stability of the battery slurry, but also significantly extends the service life of the battery. Moreover, the temperature, stirring process and slurry coating of the lithium iron phosphate slurry prepared by the present invention are uniform, the surface is smooth and free of particles, and the slurry stability and surface density stability are significantly improved.
[0104] In addition, the various modifications listed herein and the changes in the methods and compositions in the invention will be apparent to those skilled in the art without departing from the scope and spirit of the invention. Although the invention has been specifically described in conjunction with a variety of specific preferred embodiments of the invention, it should be understood that the invention should not be limited to these specific embodiments. In fact, various modifications as described above that are apparent to those skilled in the art to obtain the invention should be included within the scope of the invention.
Claims
1. A slurry for positive electrode of lithium iron phosphate battery, characterized in that: The composition comprises the following components in parts by weight: The active lithium iron phosphate material is a lithium iron phosphate material doped with a ternary material, the particle size range of the lithium iron phosphate material is 2 to 6 μm, and the mass ratio of the lithium iron phosphate material to the ternary material is 5 to 8:2 to 5; the ternary material is a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.815 Co 0.15 Al 0.035 O2、LiNi 0.88 Co 0.09 Al 0.03 One of lithium nickel cobalt aluminum oxides having a molar ratio of O2 and Ni of more than 0.9, wherein the general chemical formula of the lithium nickel cobalt aluminum oxide is LiNi x Co y Al 1-x-y O2, 0.7<x<1,0<y<0.3; The positive electrode organic auxiliary agent is an organic mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 5-7:2-3:1-2; the molecular weight of the polyethylene glycol is 200-600.
2. The positive electrode slurry for lithium iron phosphate battery according to claim 1, characterized in that: The composition comprises the following components in parts by weight: The active lithium iron phosphate material is a lithium iron phosphate material doped with a ternary material, the particle size range of the lithium iron phosphate material is 2 to 6 μm, and the mass ratio of the lithium iron phosphate material to the ternary material is 5 to 8:2 to 5; the ternary material is a high-nickel ternary material LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.815 Co 0.15 Al 0.035 O2、LiNi 0.88 Co 0.09 Al 0.03 One of lithium nickel cobalt aluminum oxides having a molar ratio of O2 and Ni of more than 0.9, wherein the general chemical formula of the lithium nickel cobalt aluminum oxide is LiNi x Co y Al 1-x-y O2, 0.7<x<1,0<y<0.3; The positive electrode organic auxiliary agent is a mixed solution formed by isopropanolamine, ethylene glycol and polyethylene glycol, the weight ratio of isopropanolamine, ethylene glycol and polyethylene glycol is 7:2:1; the molecular weight of the polyethylene glycol is 200-600.
3. The slurry for positive electrode of lithium iron phosphate battery according to claim 1, characterized in that: The rare earth oxide is at least one of oxides of lanthanum, cerium, yttrium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and scandium.
4. The slurry for positive electrode of lithium iron phosphate battery according to claim 1, characterized in that: The rare earth oxide is a mixture of lanthanum oxide, cerium oxide and neodymium oxide, wherein the mass ratio of lanthanum oxide, cerium oxide and neodymium oxide is 8:1:1; and the particle size range of the rare earth oxide is 2-4 μm.
5. The positive electrode slurry for lithium iron phosphate battery according to claim 1, characterized in that: The weight ratio of lithium iron phosphate to ternary material is 8:
2.
6. The slurry for positive electrode of lithium iron phosphate battery according to claim 1, characterized in that: The binder is polyvinylidene fluoride with a molecular weight of 1 million to 1.2 million; the positive electrode solvent is a mixed solution of polyvinyl pyrrolidone and N-methyl pyrrolidone, the mass ratio of the polyvinyl pyrrolidone to the N-methyl pyrrolidone is 1 to 2: 8 to 9, and the molecular weight of the polyvinyl pyrrolidone is 10,000 to 25,000.
7. The slurry for positive electrode of lithium iron phosphate battery according to claim 1, characterized in that: The conductive agent is a mixture of one or more of carbon nanotubes, graphene, SP, and KS-6, and the particle size of the conductive agent ranges from 2 to 4 μm.
8. A positive electrode for a lithium iron phosphate battery, characterized in that: The positive electrode of the lithium iron phosphate battery is made of the slurry for the positive electrode of the lithium iron phosphate battery according to any one of claims 1 to 7.
9. A lithium iron phosphate battery, characterized in that: It includes the lithium iron phosphate battery positive electrode as described in claim 8.
10. A method for preparing a lithium iron phosphate battery as claimed in claim 9, characterized in that: Follow these steps: Weigh 95-97 parts of active lithium iron phosphate material, 0.1-1 parts of rare earth oxide, 1-2 parts of acetylene black, 0.5-2 parts of conductive agent, 1-5 parts of binder, 2-3 parts of positive electrode organic additive and 30-40 parts of positive electrode solvent by weight; The binder is prepared into a glue solution using a cathode solvent; After the weighed rare earth oxide, acetylene black and conductive agent are dry-mixed evenly, a portion of the glue solution is slowly added, and the mixture is stirred at a speed of 15 to 30 RPM for 15 to 30 minutes to obtain a mixture A; Adding active lithium iron phosphate material and positive electrode organic additive to mixed material A in multiple times to obtain mixed material B; controlling the stirring speed to 15-80RPM in a gradient manner, and the stirring time is 1-2h; Slowly add the remaining glue to the mixture B, with a stirring speed of 15 to 80 RPM, and stir in a gradient manner for 1 to 2 hours to obtain a slurry for a positive electrode of a lithium iron phosphate battery, wherein the solid content of the slurry for a positive electrode of a lithium iron phosphate battery is 60 to 70%, the slurry viscosity is 6000 to 12000 mPa·s, and the slurry fineness is ≤20 μm; The prepared slurry was coated on a clean and dry aluminum foil using an extrusion coater at room temperature; The coated electrode sheet is placed in a vacuum oven, baked at 80-120°C for 12-16 hours, and rolled and die-cut to obtain a positive electrode sheet; The prepared electrode pieces were cut into square electrode pieces, and graphite was used as the negative electrode to prepare a full battery in a glove box filled with nitrogen.
Citation Information
Patent Citations
A process for mixing positive electrode slurry for lithium-ion batteries
CN103700861B
Cited By
Preparation and coating method of lithium ion battery pole piece coating slurry
CN120895600A